Physiological Basis and Transcriptional Profiling of Three Salt-Tolerant Mutant Lines of Rice - Domingo, Concha; Lalanne, Eric; Catalá, María M.; Pla, Eva; Reig-Valiente, Juan L.; Talón, Manuel (Frontiers in Plant Science, 2016)
Salinity is a complex trait that affects growth and productivity in many crops, including rice. Mutation induction, a useful tool to generate salt tolerant plants, enables the analysis of plants with similar genetic background, facilitating the understanding of the salt tolerance mechanisms. In this work, we generated three salt tolerant mutant lines by irradiation of a salt-sensitive cultivar plants and screened M2 plants at seedling stage in the presence of high salinity. These three lines, SaT20, SaS62 and SaT58, showed different responses to salinity, but exhibited similar phenotype to wild type plants, except SaT20 that displayed shorter height when grown in the absence of salt. Under salt conditions, all three mutants and the parental line showed similar reduction in yield, although relevant differences in other physiological parameters, such as Na+ accumulation in healthy leaves of SaT20, were registered. Microarray analyses of gene expression profiles in roots revealed the occurrence of common and specific responses in the mutants. The three mutants showed up-regulation of responsive genes, the activation of oxido-reduction process and the inhibition of ion transport. The participation of jasmonate in the plant response to salt was evident by down-regulation of a gene coding for a jasmonate O-methyltransferase. Genes dealing with lipid transport and metabolism were, in general, up-regulated except in SaS62, that also exhibited down-regulation of genes involved in ion transport and Ca2+ signal transduction. The two most tolerant varieties, SaS62 and SaT20, displayed lower levels of transcripts involved in K+ uptake. The physiological study and the description of the expression analysis evidenced that the three lines showed different responses to salt: SaT20 showed a high Na+ content in leaves, SaS62 presented an inhibition of lipid metabolism and ion transport and SaT58 differs in both features in the response to salinity. The analysis of these salt tolerant mutants illustrates the complexity of this trait evidencing the breadth of the plant responses to salinity including simultaneous cooperation of alternative or complementary mechanisms.